Mechanical properties of Heusler alloys - Everhart, Wesley (Heliyon, 2019)
Heusler alloys have been a significant topic of research due to their unique electronic structure, which exhibits half-metallicity, and a wide variety of properties such as magneto-calorics, thermoelectrics, and magnetic shape memory effects. As the maturity of these materials grows and commercial applications become more near-term, the mechanical properties of these materials become an important factor to both their processing as well as their final use. Very few studies have experimentally investigated mechanical properties, but those that exist are reviewed within the context of their magnetic performance and application space with specific focus on elastic properties, hardness and strength, and fracture toughness and ductility. A significant portion of research in Heusler alloys are theoretical in nature and many attempt to provide a basic view of elastic properties and distinguish between expectations of ductile or brittle behavior. While the ease of generating data through atomistic methods provides an opportunity for wide reaching comparison of various conceptual alloys, the lack of experimental validation may be leading to incorrect conclusions regarding their mechanical behavior. The observed disconnect between the few available experimental results and the numerous modeling results highlights the need for more experimental work in this area.